Strategi Pustakawan dalam Pemanfaatan Perpustakaan Oleh Siswa di SMA Negeri 1 Lubuk Alung Kabupaten Padang Pariaman - Putri, Ningsih Ramayana; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper discusses the Strategy of Librarians in the Use of Libraries by Students in Lubuk Alung 1 High School in Padang Pariaman Regency. The purpose of this paper is to describe the Strategy of Librarians in the Use of Libraries by Students in Lubuk Alung 1 High School in Padang Pariaman Regency. This research was conducted using descriptive methods through a qualitative approach. Data was collected through literature studies, observations and direct interviews with the Head of Library of SMA Negeri 1 Lubuk Alung, Padang Pariaman Regency. Based on the discussion in the previous chapter, it can be concluded that the Librarian's Strategy in Library Utilization by Students in Lubuk Alung 1 High School in Padang Pariaman Regency is as follows: (a) require students to become members of the library and borrow textbooks; (b) providing collections that are in accordance with the curriculum; (c) collaborating with other libraries in meeting collection needs; (d) do not apply penalties for returning late books; (e) make outdoor reading rooms; (f) creating a class library; (g) conducting tutoring activities; (h) provide virtual library services; (i) provide audiovisual services; (j) provide supporting services; and (k) organizing competitions and giving awards to students.Keywords: Strategies, Librarians, Library Utilization